Does angiogenesis play a role in the establishment of mesial temporal lobe epilepsy?. Issue 49 (April 2016) - Benini, Ruba; Roth, Raquel; Khoja, Zehra; Avoli, Massimo; Wintermark, Pia
Highlights: Mesial temporal lobe epilepsy (MTLE) is a focal epileptic disorder, and it is frequently associated with hippocampal sclerosis. Angiogenesis is implicated in the repair processes following brain injury, but may create an adverse hyperexcitable milieu favoring epileptogenesis. Angiogenesis is activated after pilocarpine-induced seizures. Blocking angiogenesis immediately following the initial insult in this animal model prevented angiogenesis and hippocampal atrophy and averted the development of clinical seizures. Abstract: Mesial temporal lobe epilepsy (MTLE) is a focal epileptic disorder that is frequently associated with hippocampal sclerosis. This study investigated whether blocking angiogenesis prevents the development of seizures and hippocampal atrophy in the pilocarpine rat model of MTLE. To block angiogenesis, a subset of animals were given sunitinib orally. Continuous video recordings were performed to identify seizures. Brains were then extracted and sectioned, and hippocampal surfaces and angiogenesis were assessed. After a latent period of 6.6 ± 2.6 days, the sham-treated pilocarpine rats presented convulsive seizures, while the pilocarpine rats treated with sunitinib did not develop seizures. Sham-treated pilocarpine rats but not sunitinib-treated pilocarpine rats had significantly smaller hippocampi. Endothelial cell counts in sham-treated pilocarpine rats were significantly greater than in controls and sunitinib-treated pilocarpine rats. Blocking angiogenesis immediately following the initial insult in this animal model prevented thus angiogenesis and hippocampal atrophy and averted the development of clinical seizures.